Revisiting grassroots innovation initiatives in Malaysia: Concepts and applications - Ng, B.K. (2017)
This paper seeks to examine the status and main challenges of grassroots innovation initiatives in a developing nation-Malaysia. It determines the concept and application of grassroots innovation model adopted in Malaysia's science and technology policies. The main research framework of this paper is conceptualised on the significant role of local projects at niche innovation (at the grassroots) takes many different forms that differs from the mainstream business paradigm.Findings from this paper indicate that a comprehensive model for grassroots innovations development-particularly that involves the participation of various innovation actors such as public sector organisations and business, community groups as well as individual householders-is remained elusive in the formulation of science and technology policies for grassroots innovations in Malaysia. In addition, the elements of shared rules and values that underpinned the social-led agenda are not clearly tackled in the existing policies. Base on this concern, this paper proposes a few policy directions to foster and upscaling the grassroots innovation initiatives in Malaysia.